Comparative Genomics of Esophageal Adenocarcinoma and Squamous Cell Carcinoma - Bandla, Santhoshi; Pennathur, Arjun; Luketich, James D.; Beer, David G.; Lin, Lin; Bass, Adam J.; Godfrey, Tony E.; Litle, Virginia R. (The Annals of thoracic surgery, 2012)
Esophageal cancer consists of two major histologic types: esophageal squamous cell carcinoma (ESCC), predominant globally, and esophageal adenocarcinoma (EAC), which has a higher incidence in westernized countries. Five-year overall survival is 15%. Clinical trials frequently combine histologic types although they are different diseases with distinct origins. In the evolving era of personalized medicine and targeted therapies, we hypothesized that ESCC and EAC have genomic differences important for developing new therapeutic strategies for esophageal cancer. We explored DNA copy number abnormalities in 70 ESCCs with publicly available array data and 189 EACs from our group. All data was from single nucleotide polymorphism arrays. Analysis was performed using a segmentation algorithm. Log ratio thresholds for copy number gain and loss were set at ±0.2 (approximately 2.3 and 1.7 copies, respectively). The ESCC and EAC genomes showed some copy number abnormalities with similar frequencies (eg, CDKN2A, EGFR, KRAS, MYC, CDK6, MET) but also many copy number abnormalities with different frequencies between histologic types, most of which were amplification events. Some of these regions harbor genes for which targeted therapies are currently available (VEGFA, ERBB2) or for which agents are in clinical trials (PIK3CA, FGFR1). Other regions contain putative oncogenes that may be targeted in the future. Using single nucleotide polymorphism arrays we compared genomic abnormalities in a large cohort of EACs and ESCCs. We report here the similar and different frequencies of copy number abnormalities in ESCC and EAC. These results may allow development of histology-specific therapeutic agents for esophageal cancer.